2011
DOI: 10.1111/j.1939-1676.2011.00786.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain Induced by a Minor Medical Procedure (Bone Marrow Aspiration) in Dogs: Comparison of Pain Scales in a Pilot Study

Abstract: Background: Bone marrow aspiration (BMA) is a clinical procedure frequently performed in dogs. Objective: To compare levels of pain intensity induced by 3 different BMA procedures using several pain scoring instruments.Animals: Sixteen healthy Beagles. Methods: A prospective experimental pilot study was conducted using blinded observers. Dogs were randomized into 3 groups: iliac BMA under sedation (Iliac-Sed, n = 4), sternum BMA under sedation (Stern-Sed, n = 4), and sternum BMA on conscious dogs without sedat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 19 publications
0
30
1
10
Order By: Relevance
“…The 4AVet is another composite measure pain score for dogs, reportedly with more interobserver variability than the Glasgow short form, but less biased by sedation. 7,8 Simple, online, practice-friendly numerical rating scales (0 to 4) for acute canine and feline pain have been developed (but not yet validated) by Colorado State University. in cats, a currently validated assessment tool is the UNESPBotucatu Multidimensional Composite Pain Scale.…”
Section: Multifactorial Clinical Measurement Instruments For Acute Pomentioning
confidence: 99%
“…The 4AVet is another composite measure pain score for dogs, reportedly with more interobserver variability than the Glasgow short form, but less biased by sedation. 7,8 Simple, online, practice-friendly numerical rating scales (0 to 4) for acute canine and feline pain have been developed (but not yet validated) by Colorado State University. in cats, a currently validated assessment tool is the UNESPBotucatu Multidimensional Composite Pain Scale.…”
Section: Multifactorial Clinical Measurement Instruments For Acute Pomentioning
confidence: 99%
“…A recent study regarding pain induced by bone marrow aspiration demonstrated that iliac aspiration seems to elicit more pain and that the sternum is the least invasive site for this procedure (Guillot et al, 2011). Although this was not the main objective of our study, we observed that the majority of the dogs (80.2%) tolerated sternal bone marrow aspiration with local anesthesia well; the highest level of discomfort was observed during the process of bone marrow suction.…”
Section: Discussionmentioning
confidence: 44%
“…All dogs were restrained in a sitting position to improve palpation and visualization of the sternum (Guillot et al, 2011) ( Figure 1A), and were systematically submitted to clipping and the skin antisepsis was performed with alcohol 70%. Local anesthesia with 0.2% lidocaine was performed in the skin and periosteum ( Figure 1B).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The objectives of our study were to compare the intensity of pain caused by 3 different BMA procedures in dogs, and to compare the results of different pain scales when used to assess this type of pain. 1 The primary hypothesis we wished to verify was whether we could adequately assess the pain associated with these procedures by using currently accepted pain scales. As sedation is well known to introduce bias in evaluations using pain scales, 3 a group of unsedated dogs was needed to assess the magnitude of the sedation effect.…”
mentioning
confidence: 99%